Covid-19 Risk Groups and Their Strategies for Navigating Information Overload During the First Year of the Pandemic in Chile [Grupos de Riesgo por Covid-19 y Sus Estrategias Para Enfrentar la Sobrecarga Informativa en el Primer Año de la Pandemia en Chile] - Rocamora-Villena, V (Universidad Nacional de Lanos, 2023)
As a part of the EIS-COVID project on the access and use of information during the COVID-19 pandemic in Chile, the objective of this paper was to ascertain how people’s informational environment was constructed during the first stage of the pandemic. It discusses the results of a qualitative study of people belonging to risk groups for COVID-19: people over 18 and under 65 with chronic diseases (hypertension and diabetes) and people 65 and over. Ninety semi-structured interviews were conducted in the Metropolitan and Valparaíso regions between September 2020 and January 2021. The results reveal the problematic nature of the information overload encountered by these groups and the strategies they used to navigate it: a) information avoidance; b) content corroboration and active search for reliable sources; and c) differentiated media use. © Esta obra está bajo una licencia Creative Commons Atribución 4.0 Internacional (CC BY 4.0). Atribución — Se debe dar crédito de manera adecuada, brindar un enlace a la licencia, e indicar si se han realizado cambios. Puede hacerlo en cualquier forma razonable, pero no de forma tal que sugiera que usted o su uso tienen el apoyo de la licenciante. Sin restricciones adicionales — No se pueden aplicar términos legales ni medidas tecnológicas que restrinjan legalmente a otras personas a hacer cualquier uso permitido por la licencia.